Blow up of Solutions for Petrovsky Equation with Delay Term - Yüksekkaya, Hazal; Pişkin, Erahan (Journal of Nepal Mathematical Society, 2021)
This work deals with a logarithmic Petrovsky equation with delay term. Under appropriate conditions, we prove the blow up of solutions in a finite time in a bounded domain. Our results are more general than the earlier results.